THE RELATIONSHIP BETWEEN LINGUISTIC AND CULTURAL COMPETENCE OF THE TRANSLATORS (KONFERENSIYA, 2026)
The effectiveness of translation depends not only on linguistic accuracy but also on the translator’s ability to interpret and convey cultural meanings embedded in the source text. Linguistic competence provides the structural and grammatical foundation for translation, while cultural competence ensures pragmatic appropriateness and semantic adequacy across cultural contexts. This article examines the interdependent relationship between linguistic and cultural competence in translation, highlighting their roles in achieving functional equivalence, preventing pragmatic failure, and enhancing communicative effectiveness. The study argues that linguistic competence without cultural awareness leads to formal but inadequate translations, whereas cultural competence without strong linguistic grounding results in interpretive inconsistency. The article emphasizes the necessity of integrating both competences in translator training.